Pedagogical interventions for braille Qur’an literacy in learners with visual impairment: A systematic literature review - Safaruddin Safaruddin; Budi Susetyo; Iding Tarsidi; Imas Diana Aprilia (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2026)
Braille Qur’an literacy is a critical competency for Muslim learners with visual impairment, yet the evidence base for effective pedagogical interventions remains fragmented and methodologically immature. This systematic literature review synthesized evidence from 23 studies addressing teaching and learning of Braille Qur’an or Braille Arabic literacy among learners with visual impairment, following PRISMA 2020 guidelines. Searches across five databases in October and November 2024 yielded 387 records; 23 met pre-specified inclusion criteria after screening. Eligible studies were categorized as primary evidence (direct Braille Qur’an pedagogy, n = 17) or secondary evidence (general Braille literacy or learning science relevant to the domain, n = 6). Quality appraisal using the standard MMAT version 2018 (Hong et al., 2018) identified one high-quality study, seven moderate-quality studies, and fifteen low-quality studies, reflecting an immature evidence base. Thematic synthesis identified four clusters: method and technique-oriented approaches (n = 10), media and assistive technology interventions (n = 6), teacher role and competency studies (n = 4), and cognitive-pedagogical framework studies (n = 3). Five critical gaps were identified across the evidence: absence of theory-grounded instructional models, fragmented outcome measurement, absence of cognitive load as a design principle, insufficient experimental rigor, and geographic concentration. Conclusions from this review are provisional, given the preponderance of low-quality primary evidence. The review provides a structured foundation for a new generation of theoretically informed, rigorously designed research in this domain.